APLIKASI DOSIS PUPUK Zn DAN LAMA INDUKSI TEKNIK SIPLO TERHADAP HASIL TANAMAN BAWANG PREI (Allium fistulosum L.) - Tri Oktaviani; Sugiarto Sugiarto; Sugianto Sugianto (AGRONISMA, 2021)
Leek cultivation extends to various regions (regions) throughout the archipelago, both planted in the high and lowlands. The dosage of Zn and the administration of Siplo induction can improve the quality of leek yields and improve nutrient elements in the soil. This study aims to determine the combination of Zn dose and duration of induction of Siplo on the growth and quality of leek. Factorial RAK (Randomized Block Design) used in this study. The first factor was giving Zn fertilizer: without giving Zn, giving Zn at a dose of 2 mg, and giving a dose of 4 mg. The second factor was Siplo induction: without Siplo induction, 30 minutes Siplo induction, and 60 minutes Siplo induction. The combination treatment of 4 mg Zn dose and SIPLO induction for 60 minutes gave better results, namely 9.21 tonnes / ha, while the control produced 7.34 tonnes / ha leek. The application of Zn fertilizer at a dose of 4 mg showed more yields of 47.37 grams / plant and was significantly different from those without Zn application of 46.47 grams per plant. Treatment of cyplo induction duration of 30 minutes and 60 minutes showed no significant difference with the control.